2016
DOI: 10.3390/ijms17050789
|View full text |Cite
|
Sign up to set email alerts
|

Functions of miRNAs during Mammalian Heart Development

Abstract: MicroRNAs (miRNAs) play essential roles during mammalian heart development and have emerged as attractive therapeutic targets for cardiovascular diseases. The mammalian embryonic heart is mainly derived from four major cell types during development. These include cardiomyocytes, endocardial cells, epicardial cells, and neural crest cells. Recent data have identified various miRNAs as critical regulators of the proper differentiation, proliferation, and survival of these cell types. In this review, we briefly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…miR-302/367 affects stem cell properties during expression at the early embryonic stage, and shows differential expression between mouse embryonic stem cells (mESCs) and human embryonic stem cells (hESCs) (Dyce, Toms & Li, 2010). Similarly, regulation by miR-17/92 is reported during cardiomyocyte proliferation (Yan & Jiao, 2016). miR-23/24 clusters play a critical role in T-cell differentiation (Kroesen et al, 2015) and miR-206/133b cluster is important for skeletal muscle development, regeneration and differentiation (Boettger et al, 2014).…”
Section: Significance Of Mirna Clusters In Health and Diseasementioning
confidence: 89%
“…miR-302/367 affects stem cell properties during expression at the early embryonic stage, and shows differential expression between mouse embryonic stem cells (mESCs) and human embryonic stem cells (hESCs) (Dyce, Toms & Li, 2010). Similarly, regulation by miR-17/92 is reported during cardiomyocyte proliferation (Yan & Jiao, 2016). miR-23/24 clusters play a critical role in T-cell differentiation (Kroesen et al, 2015) and miR-206/133b cluster is important for skeletal muscle development, regeneration and differentiation (Boettger et al, 2014).…”
Section: Significance Of Mirna Clusters In Health and Diseasementioning
confidence: 89%
“…Studies from several other laboratories have also demonstrated that miRNAs are associated with developmental programming of various organs (Zucchi et al 2013, Casas-Agustench et al 2015. The organs and tissues investigated include heart (Yan & Jiao 2016, Lock et al 2017), brain (Petri et al 2014) and several endocrine glands (pancreas, ovary, testes, hypothalamus and pituitary) (Kredo-Russo et al 2012, Voglova et al 2016. Of note, exposure to environmental toxins during human pregnancy affects miRNA expression in cord blood, which lead to increased disease susceptibility in offspring (Rager et al 2014, Gillet et al 2016).…”
Section: Mirna and Dohadmentioning
confidence: 99%
“…5 A number of studies demonstrated that elevated levels of miR-143 and miR-145 play an important role in regulating several transcription factors like octamer-binding transcription factor 4, sex-determining region Y-box 2, and KrĂŒppellike factor 4 (KLF-4) as well as promoting differentiation and simultaneously repressing proliferation of vascular smooth muscle cells. Regulation of cardiogenic gene expression by microRNA has been shown to play a prominent role in heart development.…”
Section: Micrornamentioning
confidence: 99%
“…The potential of influencing microRNA expression may therefore be utilized in management and prevention of cardiovascular diseases. 5 A number of studies demonstrated that elevated levels of miR-143 and miR-145 play an important role in regulating several transcription factors like octamer-binding transcription factor 4, sex-determining region Y-box 2, and KrĂŒppellike factor 4 (KLF-4) as well as promoting differentiation and simultaneously repressing proliferation of vascular smooth muscle cells. The significant increase in plasma levels of miR-143 and miR-145 in PICSO-treated patients together with the significant up-regulation of KLF-4 is suggestive of activation of such pathways.…”
Section: Micrornamentioning
confidence: 99%